2014
DOI: 10.3899/jrheum.130602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenotype and Outcome in Microscopic Polyangiitis Between Europe and Japan

Abstract: Phenotypes in patients with MPA were different between Europe and Japan. However, the outcomes of patient survival and renal survival were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
49
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 34 publications
8
49
3
1
Order By: Relevance
“…PF has been reported in 23% of GPA cases [52] and in 2.7–45% of MPA patients. In these cases, interstitial disease was usually identified at disease onset [7,11,1720,48,53,54]. Importantly, there is a significant predominance of MPO-ANCA in published series, i.e., 46–71% of all cases compared to 0–29% for PR3-ANCA [13,27,51,52,5456].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…PF has been reported in 23% of GPA cases [52] and in 2.7–45% of MPA patients. In these cases, interstitial disease was usually identified at disease onset [7,11,1720,48,53,54]. Importantly, there is a significant predominance of MPO-ANCA in published series, i.e., 46–71% of all cases compared to 0–29% for PR3-ANCA [13,27,51,52,5456].…”
Section: Epidemiologymentioning
confidence: 99%
“…Reasons for this particular association may include a higher prevalence of MPO-ANCA positivity and increased frequency of lung involvement and diffuse alveolar hemorrhage [11,61,62]. …”
Section: Epidemiologymentioning
confidence: 99%
“…Evolving treatment strategies have significantly improved survival and reduced morbidity for patients with AAV. Due to the rarity of AAV in childhood, much of our knowledge about outcomes, such as remission, relapse, and damage, has come from studies in adult disease (2)(3)(4)(5)(6)(7)(8)(9) or small pediatric case series (2,(10)(11)(12)(13)(14). Data from AAV studies in adults have shown remission rates as high as 90% (15) and 5-year survival rates of 80% (16).…”
mentioning
confidence: 99%
“…Previous studies have shown that immunosuppressants are used only limitedly in Japanese patients with AAV (3, 24). In particular, CYC is not frequently used in Japan for patients with MPA/renal-limited vasculitis (RLV) (24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CYC is not frequently used in Japan for patients with MPA/renal-limited vasculitis (RLV) (24, 25). The relatively low use of AZA in Japan might be associated with this relatively infrequent use of CYC.…”
Section: Discussionmentioning
confidence: 99%